Investigating the Association of Ankle Dorsiflexion Range With Y Balance Test, Single Leg Hop for Distance and Body Composition in Collegiate Athletes - Mamta Tiwari; Ashutosh Singh; Deepesh Sharma (Pamukkale Spor Bilimleri Dergisi)
Ankle sprains are prevalent among athletes, and decreased ankle dorsiflexion range of motion (ADROM) can contribute to these injuries. Various tests like the Y Balance Test (YBT), Single Leg Hop for Distance (SLHD), Weight-Bearing Lunge Test (WBLT), and Body Mass Index (BMI) are used to evaluate ankle function. The primary purpose of this study was to find out the correlation between ADROM and SLHD, WBLT, YBT, and BMI. Fifty-two collegiate athletes were recruited after eliminating athletes with a history of injuries to the lower extremities. The study discovered strong positive correlations between YBT anterior reach, ADROM (r = 0.72, p